Трансфер технологій у системі стратегічного розвитку університетів - Мрихіна, Олександра Борисівна (Національний університет "Львівська політехніка", 2018)
У дисертаційній роботі розроблено концептуальні, методологічні та методико-прикладні засади трансферу технологій з університетів у бізнес-середовище. Розроблено модель оцінювання рівня готовності технологій до трансферу з університетів у бізнес-середовище, що ґрунтується на оцінюванні споживчої цінності, конкурентоспроможності, технологічної готовності, витратності, та ризиковості. Розвинено парадигмальні засади трансферу технологій з університетів у бізнес-середовище та концептуальну модель системи стратегічного розвитку університету. Розроблено концептуальний підхід до розуміння компоненти «університет» як фрактала підсистеми освіти НІС, метод оцінювання трансферо-придатності технологій на засадах теорії надійності ієрархічно розгалужених систем. Удосконалено понятійно-категорійний апарат щодо трансферу технологій, програмну модель та механізм вибору структурно-функціональної моделі трансферу технологій з університетів у бізнес-середовище. Розвинено теоретичні засади взаємовпливу ринкових ефектів від технологій та концептуальний підхід до розуміння розвитку технологій на засадах ланцюгів перетворення знань. Диссертационная работа посвящена разработке концептуальных, методологических и методико-прикладных основ трансфера технологий из университетов в бизнес-среду. Разработана модель оценки уровня готовности технологий к трансферу из университетов в бизнес-среду, которая базируется на пяти блоках оценки технологии (потребительская ценность; конкуренто-способность; технологическая готовность; затратность; рискованность), развиты парадигмальные основы трансфера технологий и концептуальная модель системы стратегического развития университета. Разработан концептуальный подход к пониманию компоненты «университет» как фрактала подсистемы образования НИС, метод оценки трансферопригодности технологий на основе теории надежности иерархически разветвленных систем. Усовершенствованы понятийно-категорийный аппарат трансфера технологий, программная модель и механизм выбора структурно-функциональной модели трансфера технологий из университетов в бизнес-среду. Развиты теоретические основы взаимовлияния рыночных эффектов от технологий и концептуальный подход к пониманию развития технологий на основе цепей преобразования знаний. The dissertation aims at development of conceptual, methodological and applied frameworks of technology transfer from universities to the business environment. Globally acknowledged changes related to technology transfer give grounds for asserting the transition of the society to a new paradigm of technology transfer development from the standpoint of opportunities of technology development as well as from the standpoint of entrepreneurial enhancement. Universities have increasingly become the main participators of this process. Moreover, the revision of adopted approaches to technology transfer from universities to the business environment is necessary because Ukrainian universities, regardless of an enough high level of the scientific and technical potential, do not fully meet demands of the market environment and, correspondingly, do not gain the desired commercial outcome. Opportunities given to the Ukrainian higher educational institutions (particularly, to be founders / co-founders of other legal entities) outline a format of academic entrepreneurship for them. This stipulates new requirements to technology transfer from universities to the business environment as one of driving forces of a system “University – Governmental Authority – Business”. The above-mentioned aspects confirm the topicality of the chosen area of expertise, its purpose and goals. The scientific novelty of the obtained results consists in conceptual, methodological and applied recommendations for solving a problem of technology transfer from universities to the business environment. The author has developed a conceptual approach to understanding a “university” component as an element of an education sub-system of the national innovative system. This has enabled to ascertain the fractal nature of an interaction between its elements and to indicate second-order fractal sub-systems (education, research and development projects (R&D), innovations, administrative and production elements) within the “university” component. Taking into account the above-mentioned approach, the author has developed a model for assessing a level of technology readiness for transfer grounded in five components of assessing technology (consumption value; competitiveness; technology readiness; an amount of costs; riskiness). Each of them comprises assessment phases that determine technology readiness stages in the theoretical and methodical context and readiness levels in the applied context. The author has proposed a method for assessing transferability of technologies based on the reliability theory for hierarchically ramified systems grounded in application of a ramified generating function, a recurrence relation for computation of probability distributions for a number of outgoing elements of the system and the mathematical expectation for a number of outgoing elements for the system of assessing a level of technology readiness for transfer. The author has formed a mechanism for the choice of a structural and functional model of technology transfer from universities to the business environment grounded in the sale of licenses for technologies by a university, the foundation of spin-off companies by universities, technology transfer in the form of startups, concluding agreements on joint activity with/without establishing a legal entity, scientific and technical collaboration and takes into consideration a correlation between a level of consumption value and technological readiness of technology. The mechanism implies determination of variants for funding in case of the choice of one or another model for technology transfer. The author has specified a conceptual framework regarding technology transfer from universities to the business environment. The system approach to it has enabled to consider technology transfer as a field of the management theory and as a process of transferring technologies developed at a university and/or with the use of its resources to other economic entities for harnessing or application. The author has enhanced a program model of technology transfer from universities to the business environment based on an integral interrelation of methodological frameworks, applied implementation, factors of technology transfer uncertainty and the system perception of technology transfer. The author has enhanced a conception for development of technologies grounded in knowledge transformation chains that explains an influence of an intangible component of technology (knowledge) on its tangible component, which stipulates the formation of additional value. As a result, externalities may affect technology or the very technology may generate such externalities. The author has improved the technology transfer paradigm that conceptualizes the current driving role of universities in processes of technology transfer and is grounded in understanding technology as a peculiar good that contains knowledge. Activating externalities (synergies, convergences, etc.), knowledge as an intangible component are transferred together with an embodied good (technology) to further levels of its manifestation and cause technology development based on knowledge transformation chains. Using the described paradigm, the author has extended theoretical frameworks of an interrelation of externalities caused by technology transfer. The author has developed a conceptual model for a system of strategic development of a university, which contemplates a component principle of the compilation of elements connected by a structural and functional relation. These elements disclose a full cycle of planning strategic development. This model allows to focus on technology transfer as one of fundamental components of strategic development of a university and to form a strategy for university development in compliance with the current paradigm of technology transfer. The author has formed statements on providing technology transfer from universities to the business environment. The author has enhanced a model for technology transfer based on role reversal through substantiation of a model for technology transfer based on setting up an enterprise, which describes technology transfer that adheres to a “triple spiral” of the interaction within the system “University – Governmental Authority – Business” grounded in the contemporary function of technologies and the conception of “pushing technology / market attraction”. This model contemplates the system approach to technology transfer from universities to the business environment.
Трансфер технологий в системе стратегического развития университетов
Technology transfer within a system of strategic development of universities
Keywords: трансфер технологій; стратегічний розвиток університету; інноваційна діяльність; науково-дослідна розробка; дослідно-конструкторська розробка; трансферопридатність; парадигма; ринковий ефект; концептуальна модель; трансфер технологий; стратегическое развитие университета; инновационная деятельность; научно-исследовательская разработка; опытно-конструкторская разработка; трансферопригодность; парадигма; рыночный эффект; концептуальная модель; technology transfer; strategic development of a university; innovative activity; research and development project; transferability; paradigm; externality; conceptual model; 378(338.24)